The Illusion of Sustainability - Kremer, M.; Miguel, E. (Quarterly Journal of Economics, 2007)
We use a randomized evaluation of a Kenyan deworming program to estimate peer effects in technology adoption and to shed light on foreign aid donors' movement towards sustainable community provision of public goods. Deworming is a public good since much of its social benefit comes through reduced disease transmission. People were less likely to take deworming if their direct first-order or indirect second-order social contacts were exposed to deworming. Efforts to replace subsidies with sustainable worm control measures were ineffective: a drug cost-recovery program reduced take-up 80 percent; health education did not affect behavior, and a mobilization intervention failed. At least in this context, it appears unrealistic for a one-time intervention to generate sustainable voluntary local public goods provision.